THE PERSONAL NON-PROPRIETARY LABOUR RIGHTS: A CONCEPT, THE FEATURES AND A CLASSIFICATION - Kmetyk, Khrystyna; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to define a concept, the features, a classification of the personal non-proprietary labour rights in Ukraine. Research methods: the methods of comparative and documentary analysis, documentary synthesis and generalization and the cognitive-analytical method are used. Results: the authors provide a definition of a concept of the personal non-proprietary labour rights, characterizes their features and makes a classification of the mentioned rights. In addition, the authors emphasise a need for the further scientific substantiation of the possibility of independent regulation and protection of the personal non-proprietary labour rights of the employees by the labour law means and methods. Discussion: the point of views of the well-known scientists in the field of labour law of Ukraine concerning definition of a concept, the features and a classification of the personal non-proprietary labour rights were reviewed and analysed in the article.